Ultrastructure of silk threads of the water spider Argyroneta aquatica (Clerck, 1757) (Araneae, Cybeidae) in comparison with that of some mites - Shatrov, Andrey B.; Soldatenko, Elena V. (Frontiers in Arachnid Science, 2024)
Silk of the water spider Argyroneta aquatica (Clerck, 1757) was obtained in the laboratory in the form of a capturing web irrespectively of formation of a diving bell and egg cocoon. Silk threads were examined with light microscopy, scanning (SEM) and transmission (TEM) electron microscopy, as well as with atomic force (AFM) microscopy. Based on the diameter and internal organization, silk threads have been divided into five types -a, b, c, d, and e-types interlaced freely in the thread bundles taken for examinations. Threads of all types are infinitely long, nonbranched, round in shape, uniform in width through their course, and rarely found to be ruptured.Threads of the a-type are mostly straight, up to 1000 nm in diameter, and composed of a fibrillary wall enveloping an electron-dense vacuolated core, which may be occasionally absent. The wall may also become lost leaving a single core substance surrounded by a double slightly wrinkled membrane. Threads of the b-, c-, and d-types are organized nearly identical composed of a fine granular electron-light uniform material enveloped by a fine membrane. The diameter of these thread varies from max 500 nm in the b-type, 120 nm in the c-type to around 50 nm in the d-type. Threads of these types are more convoluted and more numerous than threads of the atype. Threads of the last, the e-type occur rarely and are significantly larger with diameter of around 3.5-4.5 µm. They possess the layered membranous wall surrounding a uniformly dense core. Silk of the water mites Limnochares aquatica (L., 1758) and Limnesia maculata (O.F. Müller, 1776) is composed of threads of only one type closely corresponded to the a-type threads of A. aquatica. Conversely, silk of the two-spotted spider mite Tetranychus urticae (C.L. Koch, 1836) consists of threads highly correlated with the d-type threads of A. aquatica. This finding shows that in different phylogenetic lineages of arachnids, the mechanisms of silk production are quite similar.